An improved perturbation and observation in MPPT control using buck-boost converter in solar panel - Tapri, Hidayah (2019)
This project is about designed and implemented an improved Maximum Power Point Tracking (MPPT) technique using Perturbation and Observation (P&O) for buck-boost converter in 50W output from 1kW solar panel. Direct current buck-boost circuit is also been designed and implemented in order to control the output voltage of this project. The Buck-boost circuit with a MOSFET is used as switching component to become an intermediary between circuit and Arduino board device that generates a Pulse Width Modulation (PWM) signal. In order to determine the effectiveness of this project, few testings have been conducted. Finally, the control is assessed through hardware test experiment. The results of simulation and hardware experiment showed that this control method is successful in controlling MPPT using P&O for buck-boost converter in solar panel because it is able to provide a constant DC output.